Clinical presentation and spectrum of neuroimaging findings in newborn infants with incontinentia pigmenti. (28th April 2016) - Soltirovska Salamon, Aneta; Lichtenbelt, Klaske; Cowan, Frances M; Casaer, Alexandra; Dudink, Jeroen; Dereymaeker, Anneleen; Paro‐Panjan, Darja; Groenendaal, Floris; de Vries, Linda S
Abstract : Aim: To report on the neurological presentation and neuroimaging findings in newborn infants with incontinentia pigmenti. Method: The clinical and neurological course including neuroimaging and follow‐up data of eight newborn infants with the neurological phenotype of incontinentia pigmenti were retrospectively reviewed. Results: While the clinical picture was polymorphic, the neurological manifestations were defined as encephalopathic and comprised lethargy and seizures in all but one of the infants. Magnetic resonance imaging (MRI) abnormalities were predominantly in the white matter. Diffusion‐weighted imaging (DWI) was obtained during the acute phase in seven of the eight infants, showing restricted diffusion in the deep and subcortical white matter but also in the corpus callosum, basal ganglia, thalami, cerebellum, and cerebral peduncles. Susceptibility‐weighted imaging (SWI), performed in five infants, showed a variable amount of signal loss, mainly in the white matter, within areas of restricted diffusion. Extensive MRI abnormalities in newborn infants were followed by abnormal neurodevelopment, with significant motor, cognitive, and/or visual problems. Interpretation: To assess the extent of central nervous system involvement, MRI is recommended in the clinical evaluation of infants with incontinentia pigmenti. They have a characteristic pattern of brain lesions seen on MRI, best recognized using DWI and SWI in the acute neonatal phase, which allow the identification of and distinction between ischaemic and haemorrhagic lesions. What this paper adds: Infants with incontinentia pigmenti have characteristic magnetic resonance imaging (MRI) pattern of brain lesions. These are best recognized using diffusion‐weighted imaging and susceptibility‐weighted imaging in the acute neonatal phase. MRI abnormalities are predictive of adverse neurological sequelae. Phenobarbitone often gives poor seizure control in infantile incontinentia pigmenti. This article is commented on by Poretti and Northington on pages1000–1001 of this issue. Video Podcast:https://youtu.be/hd0WP66qwIM